2019
DOI: 10.3390/ijms20071793
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid (CSF) Exchange with Artificial CSF Enriched with Mesenchymal Stem Cell Secretions Ameliorates Experimental Autoimmune Encephalomyelitis

Abstract: The complexity of central nervous system (CNS) degenerative/inflammatory diseases and the lack of substantially effective treatments point to the need for a broader therapeutic approach to target multiple components involved in the disease pathogenesis. We suggest a novel approach directed for the elimination of pathogenic agents from the CNS and, in parallel, its enrichment with an array of neuroprotective substances, using a “cerebrospinal fluid (CSF) exchange” procedure, in which endogenous (pathogenic) CSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…However, a similar EAE model in rats demonstrates immune cell (effector T cell) entry preferentially via leptomeninges through CCR5/CXCR3 signaling (Schl€ ager et al, 2016), suggesting potential species differences. Notably, exchanging diseased CSF with fresh enriched artificial CSF can ameliorate the EAE response in mice (Valitsky et al, 2019). Additional roles for the ChP in mediating immune cell responses likely exist.…”
Section: Development Of Chp Immune Functionsmentioning
confidence: 99%
“…However, a similar EAE model in rats demonstrates immune cell (effector T cell) entry preferentially via leptomeninges through CCR5/CXCR3 signaling (Schl€ ager et al, 2016), suggesting potential species differences. Notably, exchanging diseased CSF with fresh enriched artificial CSF can ameliorate the EAE response in mice (Valitsky et al, 2019). Additional roles for the ChP in mediating immune cell responses likely exist.…”
Section: Development Of Chp Immune Functionsmentioning
confidence: 99%
“…Even in the case of conditioning of stem cells culture with CSF, a novel approach is proposed to replace endogenous potentially pathogenic CSF by artificial CSF enriched with MSCs secreted factors. The treatment of EAE with MSC-secretions enriched with artificial CSF caused amelioration of the clinical symptoms [56]. Our results indicated that conditioning of MSCs with healthy, or multiple sclerosis CSF, might change the Secretome of MSCs and its immunomodulatory potential; furthermore, transplantation of MSCs to patients with different/unknown inflammatory status might promote a response impossible to foresee.…”
Section: Discussionmentioning
confidence: 74%
“…This disease has a more elevated incidence in women, between 18 and 55 years [22, 23]. Animal models have become one of the primary tools for the study of MS, being induced in different ways, including by the emulsion with Myelin Oligodendrocyte Peptide (MOG 35-55), a complete Freund adjuvant, and Mycobacterium tuberculosis [24], or with Pertussis Toxin [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been demonstrated the neuroprotective role of MSCs from different tissues in the treatment of MS models, being the EAE the most common model. Clinically, it was observed in treatment with MSCs a delay in the onset of symptoms [26, 33], improvement in motor functions [20, 34], clinical signs [24-26, 35-42], and recovery/maintenance of body weight [37, 41, 42]. The most efficient clinical response was observed when MSCs were administered during the onset of disease relative to the disease peak and in untreated animals [24, 39, 41, 43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation